THE MEDICAL RESEARCH COUNCIL NEUROMUSCULAR CENTRE FOR TRANSLATIONAL RESEARCH MITOCHONDRIAL DISEASE PATIENT COHORT STUDY UK: FROM CONCEPTUALISATION TO UTILISATION. Issue 11 (9th October 2013) - Nesbitt, Victoria; Pitceathly, Robert; Cockell, Simon; Poulton, Joanna; Rahman, Shamima; Hanna, Michael; Taylor, Robert; Chinnery, Patrick; Turnbull, Douglass; McFarland, Robert
Abstract : Background: Mitochondrial disease is a clinically heterogeneous debilitating condition with a minimum birth prevalence of 9.2 per 100, 000, and is associated with a reduced life expectancy. The variable clinical phenotype has previously hindered systematic studies making natural history studies largely anecdotal. There is currently no evidence–based treatment for mitochondrial disease. Objectives: To develop a cohort of 1000 people from across the UK with biochemically, and/or genetically, confirmed mitochondrial disease to facilitate large–scale interventional trials of drugs and novel treatments, and to assess prevention strategies. The cohort will also allow definitive studies on the transmission of mtDNA mutations, and provide longitudinal data on the natural history of the disease. Design & Methods: Following consultation with the clinical research leads, the Bioinformatics Department at Newcastle University designed and accommodated a secure database on a stand–alone dedicated server. The database is backed–up daily to a second identical, but independent server. A data custodian was appointed to oversee the maintenance, security and access to stored patient information. Research associates were employed in Newcastle and London, along with administrative support, to identify and recruit patients to the cohort study. NIHR portfolio adoption facilitated recruitment through local principal investigators at an additional 16 sites across the UK. The British Neurology Surveillance Unit and British Paediatric Neurology Surveillance Unit have been utilised to identify patients not under active follow–up at one of the three centres (Newcastle, London and Oxford) providing the NHS Highly Specialised Service for Rare Mitochondrial Diseases in Adults and Children. Written informed consent is obtained from patients with confirmed mitochondrial disease. Clinical data is recorded retrospectively and prospectively. The Newcastle Mitochondrial Disease Assessment Rating Scale is utilised whenever possible. All patient data is entered anonymously and unique identifiers are used to contact patients suitable for clinical studies.The Mitochondrial Disease Oversight Committee (MDOC), which includes an ethicist and a patient representative, was established to evaluate the scientific merit and appropriateness of applications and govern utilisation of the Cohort. Results: 988 people have been consented to the cohort to date with 120 identified through surveillance units (BNSU/BPNSU); clinical data is available on 935 (95%). 49% harbour mtDNA pathogenic mutations, 10% nDNA mutations, and 41% have confirmed biochemical defects but no genetic aetiology identified to date. The m.3243A>G mtDNA mutation is the most commonly identified genetic mutation in the cohort (22%), followed by single mtDNA deletions (12%), PEO1 (4%), m.8344A>G (3%), and common POLG mutations (3%). At present 8% are clinically asymptomatic, 57% exhibit neurological features, 32% have ophthalmological involvement, 21% have gastrointestinal disturbances, 19% have haematological anomalies, 17% have cardiac involvement, 13% suffer from endocrine dysfunction. The most common neurological features include: weakness (40%), ataxia (30%), migraine (19%), seizures (13%), pyramidal/extrapyramidal signs (6%), encephalopathy (5%), stroke–like episodes (4%), myoclonus (3%). 15 clinical studies have been approved by MDOC, involving over 250 patients with mitochondrial disease. 6 clinical guidelines have been produced and are available for download: www.newcastle–mitochondria.com/service/patient–care–guidelines. Conclusion: For the first time in the UK it is possible to access a large cohort of well–characterised patients with mitochondrial disease. The cohort provides objective data on mitochondrial disease progression, in children and adults, allowing evidence–based guidelines to be developed, and prognostic advice to be provided to patients and families. There is a vast amount of data still to be analysed that will provide systematic evidence and allow the development of disease prevention strategies.